FIELD EVALUATION OF BOTANICALS AND NEW MOLECULES ON THE INCIDENCE OF WHITEFLY POPULATION AND IMPACT OF YELLOW MOSAIC VIRUS - VINODAKUMARGOUD PATIL; P. P. SINGH; I. YIMJENJANG LONGKUMER; RAM KUMAR (The Bioscan, 2019)
Among the foliar spray of synthetic insecticides and plant products imidacloprid 17.8 SL (@ 0.005%) and thiamethoxam 25 WG (@ 0.025%) when applied thrice at fortnightly interval starting after one month of sowing, provided maximum protection to mung bean crop in minimizing whitefly population 1.9, 1.2 and 0.5 whitefly/ trifoliate leaf and 2.0, 1.5 and 0.9 whitefly/trifoliate leaf, respectively; as against 4.1, 6.6 and 4.8 whitefly/ trifoliate leaf in untreated control after first, second and third spraying, respectively. The lowest MYMV disease incidence 10.2 and 8.9 per cent was recorded with foliar application of imidacloprid 17.8 SL (@ 0.005%) at vegetative and reproductive stage, respectively which was at par to thiamethoxam 25 WG (@ 0.025%) as against 44.3 and 41.1 per cent disease incidence in untreated control at vegetative and reproductive stage, respectively. The highest seed yield of mung bean (10.8 q/ha) was obtained in imidacloprid but did not differ significantly with thiamethoxam (10.0 q/ha) as against 5.3 q/ha in untreated control. The investment in foliar application of imidacloprid 17.8 SL, profenophos 50 EC, thiamethoxam 25 WG, dimethoate 30 EC, YBSE 5% and cypermethrin 10 EC proved profitable in comparison to neem oil at 2%, at their test doses.